Experiencing Technology Enabled Empathy Mapping. (28th July 2017) - Neubauer, Daniel; Paepcke-Hjeltness, Verena; Evans, Pete; Barnhart, Betsy; Finseth, Tor
Abstract: Designing and Understanding in the Problem Space, within the Virtual Space. How do we connect with spaces and people with limited or restricted access? How do we design for a situation we have not experienced? How do we develop empathy for challenges of unprecedented magnitude? Virtual reality has been commonly used for final concept presentations and experiences, however, with its recent developments and additional technological improvements in cost and fidelity it can now be implemented earlier in the design process. The nature and complexity of certain design problems necessitates innovative applications of technology alongside the use of proven methodology. This workshop sought to establish a proven link between virtual reality and empathy which is a critical component within human centered design. Integrating VR into the front end of the design process to create empathy for the user and context (as seen in artist Chris Milk's work on immersive storytelling) as well as to conceptualize in VR (Google's Tilt Brush app for virtual reality sketching) could be the 'next development in education', disrupting traditional design curriculum. This research explores that integrating emergent technologies allows designers to develop a better sense of empathy for the user, the space, and the context and ultimately resulting in more validated and human or problem centered solutions to these scenarios. The emerging presence of VR as it can be used in collaborative spaces for social experiences (virtual project rooms are currently being pioneered by Facebook's VR social environments EG Facebook Spaces), co-creation, and collaboration across disparate and international projects and teams could become the new normal. This workshop introduced participants to VR as it can be used to create empathy and to conceptualize solutions as well as the potential to collaborate remotely. A 360° pre-recorded video scenario initially exposed participants to a design problem via Google Cardboard to test the level of empathy that can be developed from this experience. A second immersive scenario included the HTC Vive for a more in depth understanding, allowing participants to independently 'walk' through the VR environment. The focus of this workshop was on defining the problem space through immersive experience rather than conceptualizing a solution. We predicted that the immersive nature of the HTC Vive would contribute significantly more to developing empathy for the problem rather than the 360º pre-recorded video scenario. In addition, we also examined what can be achieved with a more basic device (the 360º pre-recorded video scenario). The HTC Vive limited the participants to one viewer at a time and a shorter experience, while anyone with a 'smart-phone' was able to view the google cardboard experience immediately. After all participants have viewed the HTC Vive immersive experience, the group was led in a discussion around framing the present problem within the scenario. After the group had come to an agreement on the defined problem space, they were led through an initial concept defining stage. This allowed the group to gather their initial thoughts on the solution(s) to the identified problem. The research team aimed at providing VR experiences to create a stronger sense of empathy for the participant(s) in the posed scenario. The workshop concluded with an open discussion evaluating the technology enabled empathy mapping experience and how the participants may use this methodology in their practice.